Synthesis of oligoribonucleotides with phosphonate-modified linkages - Páv, Ondřej; Košiová, Ivana; Barvík, Ivan; Pohl, Radek; Buděšínský, Miloš; Rosenberg, Ivan (Organic & biomolecular chemistry, 2011)
Solid phase synthesis of phosphonate-modified oligoribonucleotides using 2'-O-benzoyloxymethoxymethyl protected monomers is presented in both 3'→5' and 5'→3' directions. Hybridisation properties and enzymatic stability of oligoribonucleotides modified by regioisomeric 3'- and 5'-phosphonate linkages are evaluated. The introduction of the 5'-phosphonate units resulted in moderate destabilisation of the RNA/RNA duplexes (ΔT(m)-1.8 °C/mod.), whereas the introduction of the 3'-phosphonate units resulted in considerable destabilisation of the duplexes (ΔT(m)-5.7 °C/mod.). Molecular dynamics simulations have been used to explain this behaviour. Both types of phosphonate linkages exhibited remarkable resistance in the presence of ribonuclease A, phosphodiesterase I and phosphodiesterase II.
Keywords: Exonucleases; Phosphorous Acids; Molecular Dynamics Simulation; Solid-Phase Synthesis Techniques; techniky syntézy na pevné fázi; Oligoribonucleotides; Ribonuclease, Pancreatic; simulace molekulární dynamiky; exonukleasy; kyseliny fosforité; pankreatická ribonukleasa; Phosphodiesterase I; fosfodiesterasa I; oligoribonukleotidy